Corrosive Solo Self-Employment: The Qualitative and Quantitative Impact of Neo-Villeiny in the Fitness Industry - Harvey, Geraint; Rhodes, Carl; Vachhani, Sheena J. (Sociology (Oxford), 2025)
Solo self-employment (SSE) is a heterogeneous category that requires further contextual analysis across different occupations and professions. Drawing on a multiple methods study, this article reveals the corrosive impact of a specific type of SSE, that of the self-employed personal trainer (SEPT) in the UK fitness industry. SEPTs pay rent in cash and in kind and carry out (unpaid) tasks that would otherwise be undertaken by contracted employees leading to a corrosive impact on employment. Despite a dramatic increase in gym membership in the UK between 2006 and 2021, Office for National Statistics data reveal a decrease in employment in both proximal fitness industry functions and for personal trainers, alongside an increase in self-employed fitness instructors of more than 400%. Our study shows that the nature of the work of this growing SEPT workforce has a direct and negative (corrosive) impact on those undertaking the work.